Faktor-Faktor Keuangan yang Mempengaruhi Internet Financial Reporting pada Pemerintah Kabupaten/Kota di Provinsi Sumatera Selatan - Nadia Amanda; Siska Aprianti; Yevi Dwitayanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Internet Financial Reporting (IFR) may be a instrument for uncovering government money related reports by means of the web or websites possessed by neighborhood governments. Distribution of government monetary reports by means of e-Government is known as Web Monetary Announcing (IFR). The government employments the web to publish its budgetary reports as one step to extend straightforwardness. By giving get to to the open, the government looks for to appear the open how its funds are overseen. Past considers have found that the straightforwardness of neighborhood government budgetary reports is frequently impacted by the money related conditions of the locale. In this consider, IFR is measured utilizing the factors use and budgetary reliance. Board information for this think about were gotten from inspected territorial money related reports from 17 districts/cities in South Sumatra Area in 2018-2022 with a add up to investigate test of 85. Testing utilizing the SPSS 29 program. The test comes about concluded that use had an impact on web budgetary announcing, whereas budgetary reliance had no impact on  internet financial reporting (IFR).